Targeting tumor microenvironment with photodynamic nanomedicine - Modi S.K.; Mohapatra P.; Bhatt P.; Singh A.; Parmar A.S.; Roy A.; Joshi V.; Singh M.S. (My University, 2025)
Photodynamic therapy (PDT) is approved for the treatment of certain cancers and precancer lesions. While early Photosensitizers (PS) have found their way to the clinic, research in the last two decades has led to the development of third-generation PS, including photodynamic nanomedicine for improved tumor delivery and minimal systemic or phototoxicity. In terms of nanoparticle design for PDT, we are witnessing a shift from passive to active delivery for improved outcomes with reduced PS dosage. Tumor microenvironment (TME) comprises of a complex and dynamic landscape with myriad potential targets for photodynamic nanocarriers that are surface-modified with ligands. Herein, we review ways to improvise PDT by actively targeting nanoparticles (NPs) to intracellular organelles such as mitochondria or lysosomes and so forth, overcoming the limitations caused by PDT-induced hypoxia, disrupting the blood vascular networks in tumor tissues—vascular targeted PDT (VTP) and targeting immune cells for photoimmunotherapy. We propose that a synergistic outlook will help to address challenges such as deep-seated tumors, metastasis, or relapse and would lead to robust PDT response in patients. © 2024 Wiley Periodicals LLC.